Factors limiting liveweight gain of beef cattle on rangeland in Botswana - Pratchett, D.; Capper, B.; Light, D.; Miller, M.; Rutherford, A.S.; Rennie, T.; Buck, N.; Trail, J.C.M. (1977)
Evaluates the usefulness of different range parameters for establishing limiting factors to growth of beef cattle, particularly crude protein content and dry matter digestibility of herbage.